Level of Intention on Blood Donation Among NEUST Community: A Basis for Blood Type Repository - Reguyal, June Christian G.; Baguio, Hazel Mae F.; Alfonso, Katherine R.; Astelero, Kyla Ivy B.; Abella, Aaron Miguel C.; Balcos, Pamela O. (UM Purwokerto Press, 2025)
Blood is a fluid that travels to all areas of the body that pumped by the heart as well as oxygen, nutrients, and waste materials away from the cells. Therefore, the demand for human blood is high and, having a steady and varied blood supply is still challenging. Blood donation plays a crucial role in maintaining public health, guaranteeing sufficient resources. However, recognizing the distribution of different blood types within a community is imperative for successful donation initiatives.With the help of this study, the Nueva Ecija University of Science and Technology (NEUST) community will have a comprehensive blood type database, which will serve as a basis for future blood type repository aimed at enhancing community resilience and improving the health of those in need of transfusions. It also emphasizes the significance of awareness and intention in encouraging blood donation. By addressing misconceptions and barriers, future initiatives can effectively engage the NEUST community. The result of the study showed that approximately of NEUST Community were aware of their blood type and blood donation. Furthermore, the level of their intention and knowledge demonstrated by respondents regarding their blood type and the importance of blood donation enables the researchers to establish a comprehensive blood repository. Level of Intention on Blood Donation Among NEUST Community: A Basis for Blood Type Repository serves as a vital resource for potential donors and recipients within the NEUST community, facilitating timely and efficient blood transfusion services when needed.